Young scientists of the Russian Federation – participants of the all-russian forum of young inventors - M. V. Osipova; V. V. Timofeev (Современная наука и инновации)
In the article, the authors consider the issues of participation of young scientists in the events of the Festival of the All-Russian Society of Inventors and Innovators (hereinafter - VOIR) "Science and Inventions for Life", which took place in 2023 in various regions of the Russian Federation. At the same time, special attention is paid to the organization and holding of the Forum at Yaroslav the Wise Novgorod State University (hereinafter – NovSU) (Veliky Novgorod). The authors conclude that the model of holding events of this format for young scientists forms not only professional, but also additional skills in the field of communication, interaction, as well as competencies in the field of intellectual property. The advantages of the analyzed model of conducting scientific and practical events at the AllRussian level are noted in the work. The authors reveal an innovative approach to the preparation of scientific and practical events. In particular, the requirements for the organization of the competitive, expert, exhibition and congress part of the events, the algorithm of actions and the stage of implementation are revealed. It is concluded that the model of scientific and practical activities of university students should be accompanied by comprehensive interaction with the patent office.